Generalization of Numerical Equation Solutions for Wire Movement at Short Circuit Using Similarity Criteria - I. I. Sergey; E. G. Ponomarenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Equations of wire movement at short circuit in the dimensionless form have been obtained. Criteria of geometrical and dynamic similarity of equation solutions for wire movement have been determined. Generalized dependences of wire dynamic parameters on criterion of dynamic similarity that are suitable for design practice have been constructed.